GAMBARAN PERILAKU SEKSUAL BERISIKO HIV AIDS PADA PASANGAN GAY (Studi Kualitatif di Kota Semarang) - Nirmala Herlani; Emmy Riyanti; Bagoes Widjanarko (Jurnal Kesehatan Masyarakat (Undip), 2016)
Sexual behaviour risky on gay often associated with the genesis HIV AIDS in men, within the city of Semarang been an increase in prevalence of AIDS from 5% to 12 %. From January to September 2015 within the city of Semarang has happened 388 case of HIV, 38 AIDS, and 2 people died. Research aims to understands picture sexual behaviour risky HIV AIDS to a gay couple within the city of Semarang. The methods used qualitative with the methods purposive, members of Rumah Pelangi Community. The research results show that age subject starting from 16-35 years old, education subject an average high school, the average subject derived from Semarang. All subject admitted habitually do anal sex and an oral sex, on average, they have sexual intercorse 2 times a week. The average subject being gay due to be a trauma sexual harrasment from closes people. In terms of knowledge, most of the subject included in the category good enough because they are often exposed to informtion from community, in terms of attitude said inadequate because all subject think that behaviour risky espescially an oral and anal is behaviour usual and most admitted that they were not advocated a spouse wearing a condom, while in terms of practices it can be said less all because the research shows that there is the acts of sex risky, but most of them are not do VCT and not use a condom when have sex, and community provide condoms free month. Sexual behavior high risk performed by couples gay among others indicated by several things that is the acts of relating to partner before, never usea condom, the high frequency intercourse with a partner, felt himself and a spouse healthy, so there should have been monitoring further on the use of condom.